The Impact of the Flipped Classroom Model on Students' Academic Achievement - Cabı, Emine (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
The aim of this study is twofold. First, it aims to investigate the impact of the Flipped Classroom (FC) Model on students’ academic achievement. Second, it reveals the students’ opinions about the model itself. For four weeks, the students in the experimental group were taught in a blended learning context where the FC Model was applied, while the lessons in the control group were carried out through traditional blended learning. Both groups were administered a test before and after the Flipped Classroom sessions. To analyze the data, a two-way ANOVA for Mixed Measures was conducted to compare the means of test scores of each group. The results showed that there were no statistically significant differences between the scores of the two groups. Coming to classes prepared and completing the assignments in class, so that students did not need to do assignments at home, were among the positive aspects of the FC Model. The problems encountered in this model, however, are categorized under three main titles: Motivation, Content, and Learning. At the end of the study, the advantages and disadvantages of the FC Model are identified in accordance with the participants’ opinions, and necessary suggestions made.